Visualization of quantum objects in the Copenhagen interpretation: A historical-philosophical approach - Gherab-Martín, Karim (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This article deals with the importance given to verbal images in the descriptive discourse used in quantum physics and, more specifically, in the conception of scientific language defended by supporters of the Copenhagen interpretation of quantum mechanics at the beginning of the 20th century. The Copenhagen interpretation, whose roots go back to Niels Bohr's philosophical principle of complementarity, considers that subatomic phenomena cannot be evoked directly, without reference to the observational and experimental context.